EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN CABAI MERAH PADA MUSIM HUJAN DI KABUPATEN LAMONGAN, JAWA TIMUR MENGGUNAKAN INTEGRASI SISTEM INFORMASI GEOGRAFIS DAN SISTEM PENILAIAN KESESUAIAN LAHAN - Hafiz Akbar Pamungkas; Mochammad Munir (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2018)
This study that was aimed to get the land suitability class of red chili in Lamongan Regency, and determining the area that suitable to plant the red chili in rainy season, was done at Balai Besar Sumberdaya Lahan Pertanian Bogor, West Java and Lamongan Regency, East Java. This study was conducted using the integration between Geographic Information System (GIS) and Land Suitability Scoring System (LSSS). Based on LSSS program running and data that joined in ArcGIS, the results showed that there are three land suitability classes for red chili in Lamongan Regency, i.e. S1 (very suitable), S2 (fairly suitable), S3 (marginally suitable), and N (not suitable). The above classes also have the limiting factors, i.e. slope (eh1), soil texture (rc2), and soil depth (rc4). The total amount of land availability based on the forest area status, on the APL area is 153.329 ha, while that on the HP area is 29.923 ha. The total amount of land availability based on the land licensing, on the PTL area is 14.543 ha, and that on the NPT area is 151.906 ha. The area recommended for planting red chilli in the rainy season is 160.728 ha.